Die design for brace instrument panel for Perodua / Fazli Said, Zulkarnain Ariffin and Wan Sulaiman Mohd Daud - Said, Fazli; Ariffin, Zulkarnain; Mohd Daud, Wan Sulaiman (1998)
Manufacturing is the act of transforming raw material into usable products. Manufacturing Process are the specials operations by which these material transforming are achieved by cutting, forming, assembling and finishing. In this research will show the operation of manufacturing the BRACE INSTRUMENT PANEL of vehicle component for PERODUA KANCIL.